STRATEGI GURU DALAM MENGATASI KESULITAN BELAJAR SISWA PADA PELAJARAN MATEMATIKA BILANGAN BULAT KELAS IV DI SDN 04 MOMONG KABUPATEN BENGKAYANG TAHUN AJARAN 2023-2024 - Hestiani; Susilawati; Topik (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This thesis discusses teacher strategies in overcoming student learning difficulties in integer mathematics learning for fourth grade at SDN 04 Momong, Bengkayang Regency, academic year 2023-2024. Based on the initial pre-survey results that the researcher conducted with one of the teachers at SDN 04 Momong, it was stated that the teacher's strategy in overcoming student difficulties in learning integer mathematics for fourth grade at SDN 04 Momong. Students experience difficulties in learning integer mathematics, and the strategy used by the teacher is not appropriate, which will make students bored in the classroom. This fact sparked the researcher's interest in conducting research at SDN 04 Momong. The subjects in this study are the results of interviews with informants from the principal and the fourth-grade teacher at SDN 04 Momong. This research uses a qualitative approach and the phenomenology research type. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques use data reduction, data display, and conclusion drawing. The technique for checking the validity of the data uses triangulation and member check.